2002
DOI: 10.1046/j.1528-1157.2002.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizures after Spontaneous Supratentorial Intracerebral Hemorrhage

Abstract: Summary:Purpose: To characterize seizures after intracerebral hemorrhage (ICH), evaluating the risk of occurrence and relapse, predisposing factors, and prognostic significance, and to assess the utility of antiepileptic drug (AED) therapy as used in clinical practice.Methods: The study sample consisted of 761 patients with spontaneous, nonaneurysmal, supratentorial ICH. Seizures were classified as immediate (within 24 h of ICH) and early (within 30 days of ICH). Baseline variables and clinical events were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
4
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(190 citation statements)
references
References 26 publications
5
175
4
6
Order By: Relevance
“…Epilepsy is the occurrence of repeated unprovoked seizures. 4,18 We assigned our patients to 3 groups based on seizure onset relative to the clinical ictus of spontaneous ICH. Immediate seizures were defined as occurring within 24 hours of spontaneous ICH onset, early seizures as occurring within 2 weeks of ICH, and late seizures as occurring more than 2 weeks later.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epilepsy is the occurrence of repeated unprovoked seizures. 4,18 We assigned our patients to 3 groups based on seizure onset relative to the clinical ictus of spontaneous ICH. Immediate seizures were defined as occurring within 24 hours of spontaneous ICH onset, early seizures as occurring within 2 weeks of ICH, and late seizures as occurring more than 2 weeks later.…”
Section: Methodsmentioning
confidence: 99%
“…1 Epileptic seizures after spontaneous ICH have been reported in 2.8-18.7% of patients in various studies, 1,3,4,6,9,14,15,19 and seizures only in patients with strokes and cerebral hemisphere lesions. 4,18 The indications for and duration of seizure treatment required after spontaneous ICH remain controversial, although Passero et al 18 recently demonstrated that the risk of early seizures was reduced with prophylactic AED therapy in patients with lobar ICH. Some physicians consider prophylaxis with AEDs to be a standard part of care, while others are concerned about the potential adverse effects of AEDs and choose to treat seizures only when symptoms arise.…”
mentioning
confidence: 99%
“…Epilepsy developed in 43% of patients affected by seizures occurring more than 2 weeks after the onset of SICH, whereas it developed in only 17% of those with seizures appearing within 2 weeks of onset. Passero, et al, 97 retrospectively reviewed data acquired in 761 patients with supratentorial SICH and reported a 30-day actuarial risk of post-SICH seizures of 8.1%. They found that the risk of early seizures in lobar SICH was reduced by prophylactic antiepileptic drug therapy.…”
Section: Medical Treatmentmentioning
confidence: 99%
“…There was also a trend toward poorer functional outcome at discharge [116]. Treatment with antiepileptic drugs (AEDs) in lobar ICH patients is associated with a decrease in the number of clinically detectable seizures, which in theory should be beneficial [117]. However, AEDs have not been shown to improve outcome, and in fact may be associated with worse outcomes in unselected ICH patients [118,119].…”
Section: Seizuresmentioning
confidence: 99%